2016
DOI: 10.4102/sajhrm.v14i1.702
|View full text |Cite
|
Sign up to set email alerts
|

The role of big five factors on predicting job crafting propensities amongst administrative employees in a South African tertiary institution

Abstract: Orientation: Personality provides a foundation for understanding employee job behaviours. It determines and reflects how they respond to their work situations. There is a shortage of previous researches that have specifically dealt with the predictive role of personality on job crafting. Job crafting is also a significantly new concept in the South African work context. It has both positive and negative consequences on employee job behaviours.Research purpose: The present study investigated the role of big fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 21 publications
6
32
2
5
Order By: Relevance
“…Previous research has indicated, that individual factors, such as the Big Five personality traits, are predictors of job crafting. For example, increasing social job resources was significantly correlated with Agreeableness, Extraversion, and Openness to experience (Bell and Njoli, 2017). Consequently, a person with high PsyCap might craft a job more likely.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated, that individual factors, such as the Big Five personality traits, are predictors of job crafting. For example, increasing social job resources was significantly correlated with Agreeableness, Extraversion, and Openness to experience (Bell and Njoli, 2017). Consequently, a person with high PsyCap might craft a job more likely.…”
Section: Introductionmentioning
confidence: 99%
“…The three sub‐dimensions include increasing structural job resources (e.g., “I make sure that I use my capabilities to the fullest,” five items, α = 0.89), increasing social job resources (e.g., “I ask colleagues for advice,” five items, α = 0.90), and increasing challenge job demands (e.g., “I try to make my work more challenging by examining the underlying relationships between aspects of my job,” four items, α = 0.84). While job crafting research has often examined these sub‐dimensions separately, a number of studies have used aggregated scores across the sub‐dimensions to indicate overall job crafting (e.g., Bell & Njoli, ; Ingusci, Callea, Chirumbolo, & Urbini, ; Tims et al, ). Scholars have advocated aggregating the sub‐dimensions of job crafting since “job crafting represents the orchestration of related proactive behaviors that are jointly enacted,” (Rudolph et al, , p. 116).…”
Section: Methodsmentioning
confidence: 99%
“…Peral and Geldenhuys (2016), in a study among high school teachers, found that job crafting was positively related to psychological meaningfulness and work engagement. Lastly, Bell and Njoli (2016) showed that employees’ personality traits have important implications for job crafting behavior.…”
Section: The Jcsmentioning
confidence: 99%